Data from: Looking into the past – the reaction of three grouse species to climate change over the last million years using whole genome sequences - Kozma, Radoslav; Melsted, Páll; Magnússon, Kristinn P.; Höglund, Jacob (Zenodo, 2015)
Tracking past population fluctuations can give insight into current levels of genetic variation present within species. Analysing population dynamics over larger time scales can be aligned to known climatic changes to determine the response of species to varying environments. Here, we applied the Pairwise Sequentially Markovian Coalescent (PSMC) model to infer past population dynamics of three widespread grouse species; black grouse, willow grouse and rock ptarmigan. This allowed the tracking of the effective population size (Ne) of all three species beyond 1 Mya, revealing that i) early Pleistocene cooling (~2.5 Mya) caused an increase in the willow grouse and rock ptarmigan populations, ii) the mid-Brunhes event (~430 kya) and following climatic oscillations decreased the Ne of willow grouse and rock ptarmigan, but increased the Ne of black grouse and iii) all three species reacted differently to the last glacial maximum (LGM) – black grouse increased prior to it, rock ptarmigan experienced a severe bottleneck and willow grouse was maintained at large population size. We postulate that the varying PSMC signal throughout the LGM depicts only the local history of the species. Nevertheless, the large population fluctuations in willow grouse and rock ptarmigan indicate that both species are opportunistic breeders while black grouse tracks the climatic changes more slowly and is maintained at lower Ne. Our results highlight the usefulness of the PSMC approach in investigating species' reaction to climate change in the deep past, but also that caution should be taken in drawing general conclusions about the recent past. Willow grouse autosomal consensus sequence Willow grouse autosomal consensus sequence used as input for PSMC. The file was generated from a filtered bam file using the samtools mpileup, bcftools and vcfutils.pl (vcf2fq) pipeline (downgrading mapping quality for reads containing excessive mismatches (-C) to 50, minimum read depth (-d) set to 1/3 of the mean genome coverage (22) and maximum read ...